Description of Nurse's Perception of Fulfillment the Rights of People with Mental Disorders: Literature Review - Marista Fiana; Shanti Wardaningsih (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Human rights are rights that are obtained by everyone, including people with mental disorders. One form of fulfillment of human rights is to obtain health services. Nurses are the spearhead of health services, including Those who work in mental hospitals need to have a high commitment to be able to provide optimal service to their patients, considering that the patient's condition requires special treatment. Nurses' perceptions of mental disorders in general need to be known to plan an appropriate program. To review the literature on nurses' perceptions of the fulfillment of the rights of people with mental disorders. Literature review using three databases, namely Pubmed, Google Scholar, and Proquest, using the keywords "Nurse perception" and "Right" and "Mental Disorders" a total of 771 articles were obtained, with six duplicate articles, after going through the article extraction stage, the final result obtained five articles that meet the review requirements. After reviewing the literature, several outcomes were obtained, namely: Well-being and burnout of service providers, Structural and practical factors that contribute to stigma in primary care, Expectations for psychiatric services in specialist versus primary care facilities and Clinical competence, and experience and training needs are not supported. A review of this literature review can be concluded that there are still many patients who have not received their rights while being treated at the hospital, therefore there is a need for training for mental nurses and education related to the rights of people with mental disorders. Abstrak: Hak asasi manusia adalah hak yang diperoleh oleh semua orang termasuk orang dengan gangguan jiwa. Salah satu bentuk dari pemenuhan hak asasi manusia yaitu mendapatkan pelayanan hak kesehatan. Perawat merupakan ujung tombak pelayanan kesehatan termasuk mereka yang bekerja di rumah sakit jiwa perlu memiliki komitmen yang tinggi untuk dapat memberikan pelayanan yang optimal kepada pasiennya, mengingat kondisi pasien memerlukan penanganan khusus. Persepsi dari perawat terhadap gangguan jiwa secara umum perlu diketahui untuk merencanakan program yang sesuai. Untuk melakukan telaah literatur tentang persepsi perawat terhadap pemenuhan hak-hak orang dengan gangguan jiwa. Penelusuran Literatur review menggunakan 3 data base yaitu Pubmed, Google Scholar, dan Proquest, dengan menggunakan kata kunci “Nurse perception” “Right” “Mental Disorders” di dapatkan total 771 artikel, dengan duplikasi 6 artikel, setelah melalu tahap ekstraksi artikel maka hasil akhir diperoleh 5 artikel yang memenuhi syarat review. Setelah dilakukan pengkajian, literature diperoleh beberapa hasil yaitu Kesejahteraan dan kelelahan penyedia layanan, Faktor struktural dan praktik yang berkontribusi terhadap stigma dalam perawatan primer, Harapan untuk layanan kesehatan mental di fasilitas spesialis versus perawatan primer dan Kompetensi klinis, dan pengalaman serta kebutuhan pelatihan tidak mendukung. Tinjauan dari literatur review ini dapat disimpulkan bahwa masih banyak pasien yang belum mendapatkan haknya selama di rawat di rumah sakit oleh karena itu perlu adanya pelatihan kepada perawat jiwa serta edukasi terkait hak-hak orang dengan gangguan jiwa